MATERIAL INCENTIVES AND CITIZEN ENGAGEMENT IN PHILIPPINE LOCAL GOVERNANCE - Richard Ian Mark Necosia; Joanne Vivien Necosia (Yayasan Wayan Marwan Pulungan, 2026)
This study examines how barangay officials in the Philippines use ayuda, or material assistance, as a strategy to encourage citizen engagement in local governance. Using a descriptive qualitative approach, individual interviews were conducted with 28 barangay officials across Bukidnon province. Thematic analysis revealed three findings: (1) ayuda is an effective short-term motivator for participation, particularly in economically vulnerable communities, (2) officials are concerned about dependency and transactional forms of engagement, and (3) strategies such as attendance-based distribution, raffles, and food provision are commonly employed to sustain turnout. While these approaches increase citizen presence, they do not guarantee long-term and meaningful participation. This is one of the first studies to explore the perspectives of barangay officials, the implementers of ayuda, highlighting how they operationalize aid as a governance tool. The findings raise critical questions about sustainability and ethics in incentive-driven participation and recommend integrating civic education and participatory mechanisms beyond material rewards. These insights can inform policy design that balances immediate social protection with inclusive and empowered local governance.